2013
DOI: 10.1002/hep.26721
|View full text |Cite
|
Sign up to set email alerts
|

Global alterations of DNA methylation in cholangiocarcinoma target the Wnt signaling pathway

Abstract: The molecular mechanisms underlying the genesis of cholangiocarcinomas (CCs) are poorly understood. Epigenetic changes such as aberrant hypermethylation and subsequent atypical gene expression are characteristic features of most human cancers. In CC, data regarding global methylation changes are lacking so far. We performed a genome-wide analysis for aberrant promoter methylation in human CCs. We profiled 10 intrahepatic and 8 extrahepatic CCs in comparison to non-neoplastic biliary tissue specimens, using met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 38 publications
7
103
1
Order By: Relevance
“…A retrospective multicentre study published in 2013, including close to 200 patients with iCCA, concluded that intraarterial therapy was safe and this approach resulted in stable disease (62%) or partial to complete response (26%) 253 . The majority of patients were treated with conventional TACE or 90 Y-TARE, and there was no statistically significant difference in overall survival (median 13.2 months) between these two groups. In addition, 90 Y-TARE has provided partial response (27%) or stable disease (68%) in patients with iCCA 254 .…”
Section: Locoregional Therapymentioning
confidence: 93%
See 2 more Smart Citations
“…A retrospective multicentre study published in 2013, including close to 200 patients with iCCA, concluded that intraarterial therapy was safe and this approach resulted in stable disease (62%) or partial to complete response (26%) 253 . The majority of patients were treated with conventional TACE or 90 Y-TARE, and there was no statistically significant difference in overall survival (median 13.2 months) between these two groups. In addition, 90 Y-TARE has provided partial response (27%) or stable disease (68%) in patients with iCCA 254 .…”
Section: Locoregional Therapymentioning
confidence: 93%
“…The majority of patients were treated with conventional TACE or 90 Y-TARE, and there was no statistically significant difference in overall survival (median 13.2 months) between these two groups. In addition, 90 Y-TARE has provided partial response (27%) or stable disease (68%) in patients with iCCA 254 . Hepatic arterial infusion includes a catheter-based intra-arterial infusion of chemotherapeutic agents, without embolization 253 .…”
Section: Locoregional Therapymentioning
confidence: 93%
See 1 more Smart Citation
“…2) WNT signaling. The WNT pathway is highly activated in the tumor epithelium of human CCAs and is often characterized by overexpression of the ligands WNT7B and WNT10A along with several target genes (69,70). It has been demonstrated that inflammatory macrophages in the stroma surrounding the tumor are required for the maintenance of this highly activated WNT signaling status (69,71).…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…Intriguingly, the etiological origins of CCA have been shown to impact on the associated mutational landscapes, both in comparisons of liver fluke-associated and non-associated tumors [34] , as well as hepatitis-positive versus -negative tumors [35] . Epigenetic lesions, such as focal promoter-associated hypermethylation [36,37] , global loss of 5-hydroxymethylcytosine [38] and aberrant non-coding RNA expression [39,40] , also contribute to iCCA pathogenesis.…”
Section: Introductionmentioning
confidence: 99%